2023
DOI: 10.1159/000529682
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID-19 Multisystem Inflammatory Syndrome-Related Cerebral Infarction in a Pediatric Patient Managed with Decompressive Craniectomy

Abstract: Most people who are infected with the novel severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) are asymptomatic or present with mild upper respiratory symptoms. This is especially true in the pediatric population; however, rarely, a massive cytokine storm can develop causing multisystem inflammatory syndrome associated with COVID (MIS-C). Furthermore, children may also suffer from acute ischemic strokes secondary to SARS-CoV-2 infection. Here, we present a 2-year-old male who was admitted to the hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Therapeutic modalities described for COVID-19-associated AIS vary among studies, including anticoagulation, thrombolysis, steroids, immunoglobulins, remdesivir, and endovascular thrombectomy. 1,18,22,25,38 All children with AIS in the current study presented beyond the therapeutic window for intravenous tPA therapy. Likewise, Vielleux et al 18 reported that 75% of children with COVID-19-related AIS presented after the proper timing for tPA treatment.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Therapeutic modalities described for COVID-19-associated AIS vary among studies, including anticoagulation, thrombolysis, steroids, immunoglobulins, remdesivir, and endovascular thrombectomy. 1,18,22,25,38 All children with AIS in the current study presented beyond the therapeutic window for intravenous tPA therapy. Likewise, Vielleux et al 18 reported that 75% of children with COVID-19-related AIS presented after the proper timing for tPA treatment.…”
Section: Discussionmentioning
confidence: 82%
“…29 Researchers have described the coexistence of MIS-C and AIS in several children with COVID-19. 1,18,25,38 In contrast, children could develop COVID-19-related AIS in the absence of MIS-C. 1,18,22 Furthermore, analysis of data from a U.S. pediatric center between March 2020 and June 2021 revealed a 2-to 3-month time lag in the peak of stroke cases compared with a 1-to 2month lag in the peak of MIS-C cases after the surge of COVID-19 rates. 18 Taken together, the risk of AIS in the postacute phase of COVID-19 seems to depart from the risk for MIS-C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pattern is consistent with the infarction locations observed in our case, suggesting a predilection for the basal ganglia in COVID-19-related cerebral infarctions in pediatric patients. However, some cases have reported involvement of the right middle cerebral artery and right posterior cerebral artery territories, as well as the bilateral superior cerebellar arteries ( 8 , 44 ). The detailed mechanisms underlying these observations warrant further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Acute strokes are uncommonly encountered in the pediatric population with an incidence of 1.2 to 2.1 out of 100,000 [ 5 ]. During the COVID-19 pandemic, neurological complications, such as acute ischemic stroke, in the pediatric population were recognized even though there are isolated cases of acute ischemic stroke with COVID-19 in the pediatric age group [ 6 ].…”
Section: Discussionmentioning
confidence: 99%